Anticipation of Corruption through Literation Based Honest Behaviour Learning in Early Childhood Education - Hanna,; Suprajogo, Tjahjo; Kalida, Muhsin; Heriyanti,; Roshonah, Adiyati Fathu (International Journal of Psychosocial Rehabilitation, 2020)
The main problem in this paper is to change the behaviour of corrupt habits that never cease to be discussed. Even though it is a violation of the law, many actors try to convince themselves that they are not the perpetrators. The perpetrators are not careless people but those who are educated even state officials. This is assumed because understanding and knowledge of corruption have not been internalized. Therefore it is necessary to provide anti-corruption literacy in education from an early age. This article tries to provide the concept of honesty learning in early childhood with the assumption that honesty will grow in a child and develop into adulthood through habituation from an early age.